A Methodology of Optimal Sizing for Wind Solar Hybrid System - Tiwari, Avinash Nath; Dubey, Navnit (Asian Review of Mechanical Engineering, 2019)
This paper proposes a methodology to perform the optimal sizing of a wind solar hybrid system. The methodology focus at finding the configuration, between a set of systems components to satisfy the desired system reliability requirements, with the lowest possible cost. Due to large number of design setting and the sporadique nature of solar and wind energy sources it become very challenging. In the first step modelling a wind solar hybrid system is considered in the procedure of optimal sizing methodology. While in second step optimum sizing of a system is done according to the loss of power supply probability (LPSP).